The role of affect in the positive self Two longitudinal investigations of young adolescents in the United States and China. [article]. - Zhang, Xin.
This research investigated the role of American and Chinese children?s affect in the valence of their views of themselves. In 2 studies (Ns = 825 and 397), children in the United States and China reported on their affect (e.g., positive and negative emotions) and described themselves multiple times over the 7th and 8th grades. The more positive and less negative children?s affect, the more positive their descriptions of themselves over time in both studies. These pathways were more consistent than those in the reverse direction (i.e., from children?s self-descriptions to their affect). Notably, regardless of direction, the strength of the pathways was similar in the United States and China. The findings suggest that counter to some theoretical perspectives, affect is not more important in American than Chinese children?s judgments about the self. -- (from the authors)
Keywords: Pomerantz, Eva M; Setoh, Peipei; Adolescents; Self-concept.; Affect; China